An Analisys of Indonesian Political Economic Policies In National Economic Recovery Due To Global Pandemic Turbulence - Bayu Mogana Putra, Bayu Mogana Putra; Ridwan Adnan Erlangga (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2022)
The pandemic turbulence caused countries worldwide, including Indonesia, to experience economic turbulence. The research in this scientific paper focused on studying the national economic recovery policies that the Indonesian government produced as the political economy policies in the country's economic recovery after the pandemic turbulence. This scientific paper aimed to determine the effectiveness and productivity of political economy policies in the national economic recovery in Indonesia. Lastly, this scientific paper revealed the Indonesian government's political economy policies in the national economic recovery after the pandemic turbulence through three main aspects as analytical tools. Those aspects consisted of allocation, distribution, and evaluation of the implementation of the national economic recovery. Therefore, the effectiveness and productivity of the national economic recovery policies that the government implemented could be revealed through political economy policies.